Sintered Fe-Cr-Mo-Si-C alloys produced from pre-alloyed Fe-Cr based powders admixed with 4% SiC for high performance applications - A.N. Soe; P. Wila; M. Morakotjinda; T. Yotkaew; P. Karin; N. Ohtake; R. Tongsri (My University, 2021)
Abstract The use of pre-alloyed Fe-Cr based powders has been steadily increasing in the automotive industry. Mechanical properties can be tailored due to phase transformations controlled by alloying elements and cooling rates. Employing silicon carbide (SiC) as a source of alloying elements has been proved to be possible. In this study, three different pre-alloyed Fe-Cr based powders, namely Astaloy CrA, Astaloy CrL, and Astaloy CrM, were alloyed with 4 wt. % SiC powder. The powders were mixed and pressed into tensile test bars. The green compacts were sintered at 1250 °C for 45 minutes under the cracked ammonia gas and slowly cooled (<0.1°C/s) to room temperature. All experimental sintered alloys manifested a common feature resembling those of full pearlitic ductile irons, i.e., the feature consisted of black nodular particles enveloped with hyper-eutectoid steel matrix (grain boundary or pro-eutectoid cementite plus pearlite). The tensile testing indicated that Alloy-3 (Astaloy CrM + 4%SiC) was observed to have better mechanical properties in comparison with Alloy-1 (Astaloy CrA + 4%SiC) and Alloy-2 (Astaloy CrL + 4%SiC), apart from slightly lower elongation than Alloy-2. Regardless of SiC addition, the presence of chromium (Cr) content was observed to substantially influence mechanical properties and microstructure. According to the investigation of fracture surfaces by SEM, mixtures of shallow dimples and cleavage fractures were examined in the sintered alloys.
Keywords: Elongation; Powder Metallurgy Techniques and Materials